MENGINTEGRASIKAN PERMAINAN TRADISIONAL BALI (DOLANAN) PADA PENDIDIKAN ANAK SD SEBAGAI MEDIA PENDIDIKAN KARAKTER ANAK - MADE ADI NUGRAHA TRISTANINGRAT (Purwadita : Jurnal Agama dan Budaya, 2018)
This study aims: 1) to Integrating Dolanan in the local content of Primary Education is the internalization of the value of character education into learning so that the result is an awareness of the importance of values, and 2) to forming a positive character for children and habituation of personality values into the behavior of everyday learners through learning process both in and out of the classroom. Culture can not be separated from society. Culture has become a major feature of a group of people and has been ingrained. Culture includes ideas in the human mind that are ethical and aesthetic. So in reality the culture is abstract. But its application can be observed from the behavior, language and art owned by a community. The culture will remain as long as the members of the community live and continue their noble culture. Along with the development of the times, technological progress also influence the cultural pattern of a society. Instead of bringing a positive impact to the culture, it is more affect the community to other cultures that in fact contradict the original culture of Indonesia. Take a look at the current trends, the minimal shirts that women wear, the lads who speak loudly to their parents, the cigarette smoking boy, and the "old" behavior are considered taboo now as if they are legitimate and ordinary. The development of the times precisely leads to moral degradation for this nation. Technological advances that should be able to bring this country to compete with other big nations, even a boomerang that plunged this nation in the gray area. Between following western culture and amnesia with its own culture. Character education in Indonesia to date has not been successful. Meanwhile, the formation of characteristic subjects, taught at all levels of education in the design of learning still tends to lead to a single cognitive domain only. In fact, in line with the condition of the technology and science content learned, this moral education has been abandoned by many schools. Traditional games can be an alternative that can be incorporated into game activities to hone and develop matters relating to character education. The result of research that is 1) Dolanan can be integrated into the local content SD Education is the internalization of the value of character education into the learning so that the results obtained awareness of the importance of values, and 2) Dolanan can form a positive character for children and the habituation of personality values into the behavior of everyday learners through learning process both in and out of the classroom.